Purse Seine Vessel Stability Analysis Due To Fish Hatch Redesign On Consideration Of Local Wisdom Di Sinjai Regency (Journal of Pharmaceutical Negative Results, 2023)
Stability is an important indicator in the construction and operation of ships, especially on purse seine ships . In Sinjai Regency, South Sulawesi, information was obtained related to the design of kapal purse seine located in Sinjai Regency. The purse seine ship located in Sinjai Regency has a fish hatch on the deck of the ship, this was done because of the low draft of the ship. This phenomenon means that the stability of ships in sinjai district is still not taken into account. This study aims to design a purse seine ship in Sinjai which has a hatch building on the deck of the ship without changing the shape of the bow, stern and hull of the purse seine so that local wisdom regarding the shape of the bow and stern is maintained and has better stability in two cargo conditions, namely empty cargo and full cargo of the ship. The time and place of this study was carried out in January-June 2022 in Sinjai Regency. The sampling method used is the sampling method intentionally. The results of the stability analysis obtained are the the purse seine ship after the redesign taking into account local wisdom has a better stabiltas arm than the stabiltas arm of the purse seine ship model before the redesign.